2011
DOI: 10.1007/s10903-011-9477-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Birthplace on Postpartum Health and Health Services Use

Abstract: This study examined differences in health status, rates of postpartum depression, perceptions of health services, unmet service needs, and barriers to service use among women born in and outside of Canada at 6 weeks following postpartum discharge from hospital. A secondary analysis of data gathered for a longitudinal cross-sectional survey of postpartum health and service use was conducted. Data from participants recruited from two urban hospitals were used for this analysis (n = 1,045). Analyses examined diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 24 publications
(32 reference statements)
0
63
0
3
Order By: Relevance
“…The most reported barriers in quantitative studies were linguistic barriers [14,16,17,19,20], lack of information about how to access or navigate services [14,16,[18][19][20], and long wait times/lists [16,[18][19][20]. Among qualitative studies (n = 15), the most reported barriers were found to be linguistic barriers, cultural differences, and lack of information about how to access or navigate services.…”
Section: Trends In Quantitative and Qualitative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most reported barriers in quantitative studies were linguistic barriers [14,16,17,19,20], lack of information about how to access or navigate services [14,16,[18][19][20], and long wait times/lists [16,[18][19][20]. Among qualitative studies (n = 15), the most reported barriers were found to be linguistic barriers, cultural differences, and lack of information about how to access or navigate services.…”
Section: Trends In Quantitative and Qualitative Studiesmentioning
confidence: 99%
“…Women's mental health was exclusively studied only in the context of postpartum health [14,18,34]. Immigrant women were found to be more likely than Canadian-born women to rate their postpartum health as poor, and rated their number one barrier to accessing services as an inability to find appropriate care [18].…”
Section: Women-focused Studiesmentioning
confidence: 99%
“…Migrant women are at greater risk (two times more likely than native-born women) for postpartum depression (FalahHassani et al 2015). They also have significant barriers in accessing health and social services (Ganann et al 2012;Merry et al 2011;Sword et al 2006). Our findings suggest that we may be able to identify a substantial number of migrant women early in the postpartum period, who may be at risk of sustained depression while they are still engaged with the healthcare system.…”
Section: Dear Editormentioning
confidence: 99%
“…Our goal was to verify whether there are differences regarding women's perceptions about quality and appropriateness of care received between immigrant and native women, during pregnancy and postpartum. We believe that the users' perspective still offers a sensitive quality indicator of received care (Ganann et al, 2012;Jonkers et al, 2011)and helps to identify possible gaps emerging from budgetary restructuring in public health policies. Our study was conducted in Porto, the second largest city of Portugal.…”
Section: Introductionmentioning
confidence: 99%